Community Service Program: Creative Promotion Strategy of Serangan Tourism Village Through Instagram Videos - Semara, I Made Trisna; Saputra, I Putu David Adi; Chandra, I Made Krisna Adi (Institut Pariwisata dan Bisnis Internasional, 2025)
The development of digital media has opened new opportunities for destination promotion through video-based content. Serangan Tourism Village, with its maritime culture, marine tourism potential, and turtle conservation, still faces challenges in increasing its digital exposure, particularly on Instagram. Through a community service program, promotional videos were designed and produced to showcase the natural beauty, marine tourism activities, and local culture of Serangan. The videos were professionally packaged with cinematography, informative narration, and supporting music, then published mainly on Instagram. This activity aims to enhance the brand awareness of Serangan Tourism Village, expand promotional reach through collaboration with influencers and tourism communities, and encourage tourist visits. The expected outcomes are not only to strengthen the village’s image in the digital space but also to create a positive economic impact for the local community and reinforce Serangan’s position as one of Bali’s leading tourism destinations.